Self-reported maternal morbidity and associated factors among Brazilian women - Souza,Joao Paulo (2008)
PURPOSE: Demographic health surveys may constitute a valuable source of information on maternal morbidity, particularly in locations where an integrated system of epidemiological surveillance with wide geographic coverage has not yet been developed. METHODS: This study analyzed the database obtained from a national Demographic Health Survey carried out in Brasil in 1996. Data regarding how the survey was conducted, characteristics of the women interviewed who had given birth to live infants in the five preceding years, characteristics of the obstetrical care received and complications reported were evaluated. RESULTS: Responses from a weighted total of 3,635 women were analyzed. Statistically significant differences (p<0.001) were found between geographic domains for most characteristics studied. Deliveries were predominantly hospital-based throughout the whole country. Prevalence of self-reported maternal morbidity ranged from 15.5-22.9% in the various geographic domains analyzed. This geographic factor was found to be associated to differences in the occurrence of complications, generally and specifically, for cases of prolonged labour. CONCLUSION: Differences in morbidity may reflect the intricate relationship between determinants of human development and maternal health conditions.